ANALYSIS OF SAVING BEHAVIOR FOR POOR AND NON-POOR HOUSEHOLDS IN AL-AHSA GOVERNORATE, KINGDOM OF SAUDI ARABIA, 2018 - & et al, Hadid1 (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This research was aimed at analyzing the saving behavior of Saudi households in AL-HASA governorate, the eastern region of Saudi Arabia. Data was collected via questionnaire randomly distributed to a sample of 308 Saudi households. The poverty line income was estimated as equivalent to break-even level in saving function, was estimated at 10500 Saudi Riyals per month. Using OLS method consumption and saving functions for Saudi households in AL-HASA governorate were estimated.  The marginal propensity to save for poor was higher than that of non-poor households with a statistically significant difference of about 0.35. This indicates that poor households are more willing to save compared to non-poor households if income increases for both.  For the determination of factors affecting saving behavior, the study applied the binary logistic regression, using maximum likelihood method with the dependent binary dummy variable of two values defining saving and non-saving households. Results indicated that the probability of saving for non-poor households is affected positively by household income; however, both the size of household and the dwelling type realized negative effects. Hence, the probability of increased saving for a rise in household income by SR 1,000 /month was estimated at 12.5%.  In the case of an increase in the number of family members by one person, the probability of saving was less than 29.4%. The probability of saving for households living in rented houses was 60.6% less than the probability of saving for household living in their owned houses. Hence, residential rent represent an obstacle to saving for non-poor households. The most important factor influencing the probability of saving for poor households is number of family labor, where an increase in the number of workers in the poor family by one factor increases the probability of saving 34.6%.